Computer performance engineering 8th European performance engineering workshop, EPEW 2011, Borrowdale, UK, October 12-13, 2011. proceedings - Thomas, Nigel (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 8th European Performance Engineering Workshop, EPEW 2011, held in The English Lake District in October 2011. The 16 regular papers and 6 poster presentations papers presented together with 2 invited talks were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on performance-oriented design and analysis methods, model checking and validation, simulation techniques and experimental design, performability modelling and performance and power consumption tradeoffs.